Critically Evaluate Explicit Knowledge and Implicit Knowledge Learning of English Language in Chinese-Foreign Cooperative (Asian Education Studies, 2022)
With the development of internationalization and globalization, Chinese-foreign cooperative universities are established to attract more international scholars and students, and provide more chances for Chinese students to experience English Medium Instruction (EMI) courses. From the cooperative universities’ official website pages, the universities propaganda English immersion education. In that case, the learning of academic content knowledge requires students’ English proficiency level to achieve to an exact extent. Under this circumstance, it is discussed how students in the Chinese-foreign cooperative universities learn the explicit and implicit knowledge of the English language during the EMI courses in the Chinese-foreign cooperative universities, and how the two learning modes interface with each other.